2019
DOI: 10.1177/2055102919860635
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of enhanced recovery after surgery in general gynaecology patients: An interpretative phenomenological analysis

Abstract: There is little qualitative research exploring non-cancer gynaecology patients’ experiences of enhanced recovery after surgery (ERAS) protocols. Seven women participated in audio-recorded interviews, discussing their experiences of enhanced recovery after surgery for gynaecological surgery. Data were transcribed and analysed using interpretative phenomenological analysis. Three themes were identified: meeting informational needs, taking control of pain, and mobilising when feeling fragile. Control emerged as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(47 citation statements)
references
References 26 publications
0
20
0
1
Order By: Relevance
“… 48 49 Studies have shown that a better understanding of patients' perceptions and how these influence adherence to ERAS protocols can enable specific recommendations to be made for ERAS implementation, which has a positive effect on improving the quality of ERAS implementation. 33 41 42 It is pertinent to highlight that the authors did not observe any demarcation of experience based on the year of publication. Patients’ experiences with the ERAS programme from 2003 were consistent with experiences reported in articles published as recently as 2021.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“… 48 49 Studies have shown that a better understanding of patients' perceptions and how these influence adherence to ERAS protocols can enable specific recommendations to be made for ERAS implementation, which has a positive effect on improving the quality of ERAS implementation. 33 41 42 It is pertinent to highlight that the authors did not observe any demarcation of experience based on the year of publication. Patients’ experiences with the ERAS programme from 2003 were consistent with experiences reported in articles published as recently as 2021.…”
Section: Discussionmentioning
confidence: 85%
“… 34 In addition, effective pain management enables patients to perform rehabilitation therapy as soon as possible after surgery to promote their physical recovery. 33 However, greater consideration of patients’ negative experience can increase awareness of issues that patients experience but that are not easily identified by clinicians, such as the psychological burden of early discharge. At the same time, examining and evaluating ERAS from the patient’s perspective can reveal the omissions and deficiencies of healthcare professionals in clinical care so that problems in patients’ recovery process can be solved in a timely manner, reducing potential barriers to the implementation of accelerated recovery and providing patients with good perioperative support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This psychological state could influence the patient’s return to the basic state and especially in gynaecological surgery where the psychological aspect of rehabilitation can play an important role. In two qualitative studies published by Archer,35 36 the women interviewed reported a need for control, understanding of the instructions and the expected beneficial effect. This encouraged their adherence to the ERAS programme.…”
Section: Discussionmentioning
confidence: 99%
“…O autor destaca que para os pacientes foi difícil num primeiro momento colocar em prática alguns cuidados preconizados pelo ERAS, principalmente em relação a deambulação, em decorrência da ferida operatória e da algia, porém com a ajuda do fisioterapeuta e os estímulos dos profissionais da enfermagem, tornou-se possível sair do leito e deambular precocemente, o que beneficiou a recuperação cirúrgica. Outro fator que os pacientes relataram como importante foi o protagonismo no controle da dor, ou seja, só recebiam analgésicos quando consideravam que era necessário, bem como opiáceos somente se algia intensa 23 . compreensível levando-se em conta que é a partir do histórico de enfermagem que são realizadas as demais etapas da assistência de enfermagem como a identificação dos diagnósticos e a realização da prescrição do paciente 35 .…”
Section: Pesquisa Realizada Por Mcevoy Et Al Utilizando Como Base O P...unclassified